Beyond clinical changes: Rehabilitation-induced neuroplasticity in MS. (September 2019) - Prosperini, Luca; Filippo, Massimiliano Di
Background: Neural plasticity represents the substrate by which the damaged central nervous system (CNS) re-learns lost behaviors in response to rehabilitation. In persons with multiple sclerosis (MS), rehabilitation can therefore exploit the potential of neural plasticity to restore CNS functions beyond the spontaneous mechanisms of recovery from MS-related damage. Methods: Here, we reviewed the currently available evidence on the occurrence of mechanisms of structural and functional plasticity following rehabilitation, motor, and/or cognitive training. We presented both data gained from basic laboratory research on animal models and data on persons with MS obtained by advanced magnetic resonance imaging (MRI) techniques. Results: Studies on physical and environmental enrichment in experimental MS models showed beneficial effects mediated by both immune modulation and activity-dependent plasticity, lowering tissue destruction and restoring of CNS network function. Translational researches in MS people demonstrated structural and/or functional MRI changes after various interventions, but their heterogeneity and small sample sizes (5–42 patients) raise concerns about the interpretation and generalization of the obtained results. Discussion: We highlighted the limitations of published studies, focusing on the knowledge gaps to be filled in terms of neuropathological correlations between changes detected in animal models and changes detected in vivo by neuroimaging.